Analisis Sistem Pendukung Keputusan Menentukan Produk Terlaris dengan Metode Simple Additive Weighting - Siagian, Yessica; Kifti, Wan Mariatul; Hutahaean, Jeperson (STIKOM Tunas Bangsa Pematangsiantar, 2021)
This study aims to recommend the best-selling Milk in CV. Sempurna based on criteria determined by using the technique of decision support system. Mechanical multi-criteria decision-making is based on the theory that each alternative consists of a number of criteria that have values and each criterion has weights illustrates how important these criteria with the other criteria. The final results obtained from this decision support system will provide an alternative, to recommend the best-selling Milk Product Selection in CV. Sempurna. The Best Milk Product Name SAW was Carnation Coffee-Mate Id 48x495g obtaining ranked first, next Bear Brand RTD Tin 30x189 Ml and Nestle Miss Plain Sbc Can 48x370 Gr rated two and three.